A New Isometric Exercise Training Induced Reductions of Resting Blood Pressure in Hypertensive Patients- An Exploratory Study - Hooi, Lim Boon (International Journal of Psychosocial Rehabilitation, 2020)
Exercise training programs represent a broadly recommended element in the prevention and treatment to reduce resting blood pressure (BP) may have significant implications for management of hypertension. A developing body of evaluationindicates that isometric exercise training (IET), albeit conducted predominantly in a lab setting, is effective at decreasing resting BP. The main goal of this research study was to explore whether 12-week of their brand new IET (360° TitaniUM Core Power Exercise®) may elicit clinically important discounts (≥2 mmHg) in resting BP among hypertensive patients. 10 hypertensive participants were recruited from University of Malaya and neighbourhood community practice through email, posters and advertising. They have been included if they: (a) had a medical diagnosis of primary or idiopathic hypertension; (b) currently on anti-hypertension medications (β-blockers or/and non-dihydropyridine calcium channel blockers). Standards: a) not on hypertensive medication. b) had aims organ damage (i.e. heart failure, renal failure, hypertensive retinopathy or stroke).c) has some joint mobility problem particularly the shoulder. Participants coached 3 sessions for 12 weeks, 1 session/week they completed their intervention at the lab guided by the researcher and 2 sessions/week doing the new IET in the home. The new IET consisted of twelve core exercises and the participants completed the exercises in sequence with every workout session consisted of 10-20 seconds/exercise progressively, and 3 sets each session with all the rest phase of one minute between sets. Results shows 12 weeks of lab visits and home of fresh IET induced animportantdecrease in resting BP (Systolic Blood Pressure–SBP, Diastolic Blood Pressure-DBP & Mean Arterial Pressure-MAP) in medicated hypertensive patients. The finding in this research revealed that the reductions of resting BP had been ≥2 mmHg, it helped several studies utilized IET to makedecreases in resting BP in the healthy participants along with medication hypertensive patients. In conclusion, such an easily available and affordable IET programme might helps in lower a number of the major obstacles known to decreasecoaching adherence and will offer a more efficient lifestyle improvement to the prevention and treatment of hypertension.